Explorando a Intersecção entre Economia Circular, Gastronomia e Sustentabilidade: Uma Revisão do Discurso Atual - Moura, Andreia (2024)
The purpose of this research is to examine the scienti c production and international trends and recommendations on circular economy, gastronomy, and sustainability concepts. A bibliometric analysis was carried out in the SCOPUS and Web of Science (WOS) databases, and the extracted results considered relevant were processed in the VOSviewer software. In a total of four hundred articles considered, Italian, Spanish and American authors are responsible for most of the research carried out. There has been a growing evolution in scienti c production in the last decade, due to the contribution of three hundred authors to the theme, and the main agencies that nancially support research are of European origin. Findings uncover eight crucial areas that emphasize the intricate relationship among these concepts. While the circular economy is inherently connected to sustainability, a noticeable disparity arises when compared to concepts like gastronomy and tourism. The association between the circular economy and the central tenet of sustainability, though present, seems somewhat distant, and also leaning closer to restaurants than encompassing the broader eld of gastronomy. These results help to systematize the characteristics of the scienti c literature produced on the theme and raise awareness to the importance of circular practices in the restaurant sector and serve as a guideline for entrepreneurs and managers in choosing more sustainable and eco-e cient operating alternatives. It is the rst study that addresses the intersection of circular economy and local gastronomy as a contribution to a more sustainable restaurant sector.